2022
DOI: 10.1007/s13596-021-00627-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neuroprotective effects of Canna indica L against aluminium chloride induced memory impairment in rats

Abstract: Memory disorders are the progressive neurological disorder, mainly causing dementia, memory loss and cognitive dysfunctions. The current study is aimed to experimentally validate the crude extract of Canna indica aerial parts (CIA) and root (CIR) against aluminium chloride induced altered memory in rats. Initially, methanolic extract of CIA, hydroalcoholic extract of CIR, and their combination of CIA + CIR were screened for Invitro antioxidant activity via 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…The EPM test was used in this work to evaluate memory function, and it was found that AlCl 3 rats showed considerable memory loss. The results are similar with previously published studies on memory loss caused by aluminium [ 24 , 25 ]. In contrast, TRF therapy prevented memory loss in AlCl 3 rats.…”
Section: Discussionsupporting
confidence: 93%
“…The EPM test was used in this work to evaluate memory function, and it was found that AlCl 3 rats showed considerable memory loss. The results are similar with previously published studies on memory loss caused by aluminium [ 24 , 25 ]. In contrast, TRF therapy prevented memory loss in AlCl 3 rats.…”
Section: Discussionsupporting
confidence: 93%
“…Nehru and Anand ( 2005 ) observed that decreased activities of SOD and CAT in rat’s brains exposed to AlCl 3 may be attributed to a decrease in the synthesis of enzyme proteins. Similarly, numerous studies stated that declines in activities of SOD and CAT are connected with AD (Jadhav and Kulkarni 2022 ; Ekundayo et al 2022 ; Ojha 2023 ; Chen et al 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…Our findings indicated an increase in brain TNF-α and IL-1β, which may be related to an increase in oxidative stress induced by aluminum in the AlCl 3 group. According to Popa-Wagner et al ( 2013 ), ROS produced in brain cells can alter synaptic and non-synaptic transmission among neurons, leading to neuro-inflammation, cell death, neuro-degeneration, and memory loss. Previous studies have shown that neuro-inflammatory cytokines reduce the efflux transfer of amyloid (A β) , which results in increased A β concentrations in the brain (Blasko et al 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of ACh and BuCh, which are neurotransmitters involved in normal functioning of the brain, is found to decrease in AD pathological state due to quick hydrolysis by AChE and BuChE, respectively [35]. The in vitro AChE decreases in concentration of photobiomodulation on the cerebral cortex and hippocampus.…”
Section: Discussionmentioning
confidence: 99%